Elevating Biomedical Performance of ZnO/SiO2@Amorphous Calcium Phosphate ‐ Bioinspiration Making Possible the Impossible. (17th August 2016) - Nguyen, Duc‐Viet; Jiang, Shengwei; He, Chengyong; Lin, Zhongning; Lin, Naibo; Nguyen, Anh‐Tuan; Kang, Lifeng; Han, Ming‐Yong; Liu, Xiang‐Yang
Abstract : Here a biomimetic approach is presented to fabricate nanodragon fruits featured by a multitude of tiny quantum dot ZnO seeds embedded in mesosilica (SiO2 ) flesh then enclosed in amorphous calcium phosphate (ACP) shell. The nanodragon fruits give rise to a new class of hybrid ZnO/SiO2 @ACP nanocomplex with multimoidal capability: cellular delivering, intracellular targeting, and subcellular imaging. With this particular design, the unusual fluorescent stability of ZnO quantum dots (QDs) in aqueous solution, the specific color selection of the functional ZnO QD seeds, and the stability of transient ACP over a long period of time are made possible. In addition, the nanodragon fruits, capable of targeting mitochondria, have elevated biocompatibility, thus can be of enormous potential applications in treating mitochondrial diseases including inflammation, neurodegeneration, obesity, diabetes, cardiovascular diseases, and cancer. As numerous human disorders are often associated with cellular dysfunctions, this biocompatible carrying platform, capable of delivering, targeting, and imaging subcellular organelles, is therefore highly desirable for efficacious therapeutic and diagnostic treatment. Abstract : Nucleation and its controlling factors, e.g., supersaturation, pH, solvents, and additives are applied in designing and engineering the seed‐flesh‐shell structure of ZnO–SiO2 –amorphous calcium phosphate, namely, ZnO/SiO2 @ACP nanodragon fruits with stable fluorescent properties in aqueous solution, precise color selection, and multimoidal capability: cellular delivering, intracellular targeting, and subcellular imaging.